Relationship Between Performance Management Practices and Organizational Effectiveness in Kabale District Uganda: A Case Study of Stanbic Bank. - Orikiriza, Brendah (Kabale University, 2023)
Little attempt has been made to provide a systematic discussion on the relationship between performance management practices and organizational effectiveness of Stanbic Bank in Kabale District. The purpose of this study was therefore to assess the relationship between performance management practices and organizational effectiveness of Stanbic Bank in Kabale District, South-western Uganda. The study was guided by the specific objectives which include exploring the relationship between performance planning and organizational effectiveness, investigating the relationship between performance monitoring and organizational effectiveness, and establishing the relationship between performance evaluation and organizational effectiveness. The study used descriptive research design utilizing both qualitative and quantitative data collection and analysis methods. Using simple random and purposive sampling techniques, a total of 30 respondents were selected to participate in the study. Questionnaires, key informant interviews, and observation methods of data collection were used in this study. The study findings presented revealed that 60% of the respondents noted that performance planning creates priorities to deliver efficiently in the organization, 50% of the respondents recorded that it provides direction for work efforts and leads to less time spent in the office whereas 57% 47% agreed it leads to forecast of the success and ensures that there is alignment between committees respectively. Based on the findings of the study, 67% of the respondents said that performance monitoring ensures right and on course in meeting the objectives and performance targets, 60% said it supports internal planning and development and ensures the high availability and high performance of applications, whereas 57% said that performance monitoring helps to see how inputs are utilized and 47% agreed it checks whether there is positive change or negative change. It was also found that 73 % of the respondents said that performance evaluation manages people and maximizes profitability, 67% said it helps in telling the costs incurred 60% said that performance evaluation examines performance according to the set goals 57% said that performance evaluation helps managers assess that what was contracted and 53% said it achieves information for promotion, demotion, and development. It was recommended that Banks should incorporate and invest in technology since technology is an important aspect in the alignment of information systems with business strategy.